How does Haskell evaluate this function defined with partial application? - haskell

I'm trying to understand how Haskell evalutes pp1 [1,2,3,4] to get [(1,2),(2,3),(3,4)] here:
1. xnull f [] = []
2. xnull f xs = f xs
3. (/:/) f g x = (f x) (g x)
4. pp1 = zip /:/ xnull tail
I start like this:
a) pp1 [1,2,3,4] = (zip /:/ xnull tail) [1,2,3,4] -- (rule 4).
b) (zip /:/ xnull tail) [1,2,3,4]
= (zip (xnull [1,2,3,4]) (tail) [1,2,3,4]) -- (rule 3)
c) -- I'm not sure how to continue because xnull receives a function
-- and a param, and in this case it only receives a param.
Any help?

Just keep expanding:
pp1 [1, 2, 3, 4] = zip /:/ xnull tail $ [1, 2, 3, 4]
-- inline (/:/) f g x = f x (g x)
-- f = zip, g = xnull tail, x = [1, 2, 3, 4]
-- therefore:
= zip [1, 2, 3, 4] (xnull tail $ [1, 2, 3, 4])
-- inline the definition of xnull and note that the argument is not null
-- so we just want f x, or tail [1, 2, 3, 4]
= zip [1, 2, 3, 4] (tail [1, 2, 3, 4])
-- evaluate tail
= zip [1, 2, 3, 4] [2, 3, 4]
-- evaluate zip
= [(1, 2), (2, 3), (3, 4)]
Operator presidence matters. You didn't specify the associativity of (/:/) so it was defaulted to be relatively weak. Therefore, (xnull tail) bound tighter than (/:/).
Also, as a side note, (/:/) already exists in the standard library as (<*>) from Control.Applicative. It's sufficiently general so this might be difficult to see, but the Applicative instance for Reader (or perhaps better understood as the function Applicative) provides this exact instance. It's also known as ap from Control.Monad.
zip <*> tail :: [b] -> [(b, b)]
zip <*> tail $ [1, 2, 3, 4] = [(1, 2), (2, 3), (3, 4)]

This is wrong
b) (zip /:/ xnull tail) [1,2,3,4] = (zip (xnull [1,2,3,4]) (tail) [1,2,3,4]) (rule 3)
because it should be
b) (zip /:/ xnull tail) [1,2,3,4] = (zip [1,2,3,4] (xnull tail [1,2,3,4])) (rule 3)
The mistake lies in reading zip /:/ xnull tail as in (zip /:/ xnull) tail rather than zip /:/ (xnull tail).

I know this has got a bit old. But anyway, here's my take..
It helps to see the definition
pp1 = zip /:/ xnull tail
= (zip) /:/ (xnull tail)
= (/:/) zip (xnull tail)
Note the parenthesizes around (xnull tail) indicating function application having higher precedence the infix operators.
Now the definition of (/:/) is to return another function q that would take an argument x and return the result of applying the function returned by partially applying its first argument r to what is returned from applying its second argument s.
That is f would need to be able to take at least 2 arguments, while g need only take at least 1.
(/:/) f g = q
where
q x = r s
where
r = f x
s = g x
Note that r is f x, so q x is f x s.
It would have been clearer to write
f /:/ g = (\x -> f x (g x))
Now given
pp1 = zip /:/ xnull tail
we can expand to
pp1 = q
where
q x = r s
where
r = zip x
s = xnull tail x
or
pp1 = (\x -> zip x $ xnull tail x)
The rest is just replacing x with [1,2,3,4] and do the evaluations.

Related

Understanding the work of foldr and unfoldr

I have hard time understanding how these bits of code work.
"Map" function must apply the function to all elements in given list, and generate list consist of results of applying. So we are giving our function f and some list, then in lambda expression our list transforms into head "x" and tail "xs", we applying function "f" to x and append it to "xs". But what happens next? How and what exactly foldr takes for its second argument (which must be some starting value usually). And for what purpose empty list?
And function "rangeTo" : we are creating lambda expression, where we are checking that we are over the end of range, end if we are than we are giving Nothing, or if we are not at end, we are giving pair where first number append to resulting list, and second number used as next value for "from". Is it all what happens in this function, or I'm missing something?
--custom map function through foldr
map :: (a -> b) -> [a] -> [b]
map f = foldr (\x xs -> f x : xs) []
--function to create list with numbers from first argument till second and step "step"
rangeTo :: Integer -> Integer -> Integer -> [Integer]
rangeTo from to step = unfoldr (\from -> if from >= to then Nothing else Just (from, from+step)) from
To understand How foldr operates on a list. It is better to write down the definition of foldr as
foldr step z xs
= x1 `step` foldr step z xs1 -- where xs = x:xs1
= x1 `step` (x2 `step` foldr step z xs2) -- where xs = x1:x2:xs2
= x1 `step` (x2 `step` ... (xn `step` foldr step z [])...) -- where xs = x1:x2...xn:[]
and
foldr step z [] = z
For your case:
foldr (\x xs -> f x : xs) []
where
step = (\x xs -> f x : xs)
z = []
From the definition of foldr, the innermost expression
(xn `step` foldr step z [])
is evaluated first, that is
xn `step` foldr step z []
= step xn (foldr step z [])
= step xn z
= step xn [] -- z = []
= f xn : [] -- step = (\x xs -> f x : xs)
= [f xn]
what happens next? The evaluation going on as
x(n-1) `step` (xn `step` foldr step z [])
= step x(n-1) [f xn]
= f x(n-1) : [f xn]
= [f x(n-1), f xn]
untill:
x1 `step` (x2 ...
= step x1 [f x2, ..., f xn]
= [f x1, f x2, ... f xn]
So we are giving our function f and some list, then in lambda expression our list transforms into head "x" and tail "xs", we applying function "f" to x and append it to "xs".
This is not the case. Look closely at the implementation:
map :: (a -> b) -> [a] -> [b]
map f = foldr (\x xs -> f x : xs) []
There is an implied variable here, we can add it back in:
map :: (a -> b) -> [a] -> [b]
map f ls = foldr (\x xs -> f x : xs) [] ls
map takes two arguments, a function f and a list ls. It passes ls to foldr as the list to fold over, and it passes [] as the starting accumulator value. The lambda takes a list element x and an accumulator xs (initially []), and returns a new accumulator f x : xs. It does not perform a head or tail anywhere; x and xs were never part of the same list.
Let's step through the evaluation to see how this function works:
map (1+) [2, 4, 8]
foldr (\x xs -> (1+) x : xs) [] [2, 4, 8] -- x = 8, xs = []
foldr (\x xs -> (1+) x : xs) [9] [2, 4] -- x = 4, xs = [9]
foldr (\x xs -> (1+) x : xs) [5, 9] [2] -- x = 2, xs = [5, 9]
foldr (\x xs -> (1+) x : xs) [3, 5, 9] [] -- xs = [3, 5, 9]
map (1+) [2, 4, 8] == [3, 5, 9]
The empty list accumulates values passed through f, starting from the right end of the input list.
And function "rangeTo" : we are creating lambda expression, where we are checking that we are over the end of range, end if we are than we are giving Nothing, or if we are not at end, we are giving pair where first number append to resulting list, and second number used as next value for "from". Is it all what happens in this function, or I'm missing something?
Yes, that's exactly what's going on. The lambda takes an accumulator, and returns the next value to put in the list and a new accumulator, or Nothing if the list should end. The accumulator in this case is the current value in the list. The list should end if that value is past the end of the range. Otherwise it calculates the next accumulator by adding the step.
Again, we can step through the evaluation:
rangeTo 3 11 2 -- from = 3, to = 11, step = 2
Just (3, 5) -- from = 3
Just (5, 7) -- from = 3 + step = 5
Just (7, 9) -- from = 5 + step = 7
Just (9, 11) -- from = 7 + step = 9
Nothing -- from = 9 + step = 11, 11 >= to
rangeTo 3 11 2 == [3, 5, 7, 9]

Converting `do notation` to >>= v. map

Given the following do notation code:
do
a <- return 1
b <- [10,20]
return $ a+b
Is there a more idiomatic conversion:
ghci> return 1 >>= (\x -> map (+x) [10, 20])
[11,21]
versus
ghci> return 1 >>= (\x -> [10, 20] >>= (\y -> [y+x]))
[11,21]
do notation maps to monadic functions, so strictly you'd write
return 1 >>= (\a -> [10, 20] >>= (\b -> return $ a+b ))
Now, you can replace that >>= … return by just fmap
return 1 >>= (\x -> fmap (\y -> x+y) [10, 20])
and use sections, and scrap that constant 1 right into the function
fmap (1+) [10, 20]
Alternatively, if you really want to take your first summand from a list, I'd recommend to use liftM2:
liftM2 (+) [1] [10, 20]
A bit more idiomatic than this, and with the same results, is the Applicative instance of lists:
(+) <$> [1] <*> [10, 20]

A simple version of Haskell's map

I'm trying to define map in ghci recursively. What I've come up with so far is the following:
let mymap f (x:xs) = if null xs then [] else f x : map f xs
What I'd like to do now is to simplify it a bit and hardcode the list inside the code, i.e., write a map function which takes a function as argument and does what the real map does but only to a specific list e.g., [1, 2, 3, 4, 5].
Is such a thing possible?
First of all, your map function isn't entirely correct. If I were to input mymap (+1) [1], I would expect to get [2] back, but instead I'd get []. If I tried mymap (+1) [], my program would crash on a pattern match failure, since you haven't defined that case. Instead, consider defining your mymap as
mymap :: (a -> b) -> [a] -> [b]
mymap f [] = []
mymap f (x:xs) = f x : mymap f xs
If you want to do it inline with an if statement then you'd have to do
mymap f xs = if null xs then [] else f (head xs) : mymap f (tail xs)
These do essentially the same thing, but the first is a bit easier to read in my opinion.
If you want to use mymap to define a function that maps only over a specific list, you could do so pretty easily as
mapOnMyList :: (Int -> b) -> [b]
mapOnMyList f = mymap f [1, 2, 3, 4, 5]
Or in point-free form
mapOnMyList = (`mymap` [1, 2, 3, 4, 5])
using mymap as an infix operator. This is equivalent to flip mymap [1, 2, 3, 4, 5], but the operator form is usually preferred since flip is not necessarily free to execute.
You can also do this using list comprehensions:
mymap f xs = [f x | x <- xs]
Or if you want to hard code the list
mapOnMyList f = [f x | x <- [1, 2, 3, 4, 5]]

Nested loop equivalent

I want to do a list of concatenations in Haskell.
I have [1,2,3] and [4,5,6]
and i want to produce [14,15,16,24,25,26,34,35,36].
I know I can use zipWith or sth, but how to do equivalent of:
foreach in first_array
foreach in second_array
I guess I have to use map and half curried functions, but can't really make it alone :S
You could use list comprehension to do it:
[x * 10 + y | x <- [1..3], y <- [4..6]]
In fact this is a direct translation of a nested loop, since the first one is the outer / slower index, and the second one is the faster / inner index.
You can exploit the fact that lists are monads and use the do notation:
do
a <- [1, 2, 3]
b <- [4, 5, 6]
return $ a * 10 + b
You can also exploit the fact that lists are applicative functors (assuming you have Control.Applicative imported):
(+) <$> (*10) <$> [1,2,3] <*> [4,5,6]
Both result in the following:
[14,15,16,24,25,26,34,35,36]
If you really like seeing for in your code you can also do something like this:
for :: [a] -> (a -> b) -> [b]
for = flip map
nested :: [Integer]
nested = concat nested_list
where nested_list =
for [1, 2, 3] (\i ->
for [4, 5, 6] (\j ->
i * 10 + j
)
)
You could also look into for and Identity for a more idiomatic approach.
Nested loops correspond to nested uses of map or similar functions. First approximation:
notThereYet :: [[Integer]]
notThereYet = map (\x -> map (\y -> x*10 + y) [4, 5, 6]) [1, 2, 3]
That gives you nested lists, which you can eliminate in two ways. One is to use the concat :: [[a]] -> [a] function:
solution1 :: [Integer]
solution1 = concat (map (\x -> map (\y -> x*10 + y) [4, 5, 6]) [1, 2, 3])
Another is to use this built-in function:
concatMap :: (a -> [b]) -> [a] -> [b]
concatMap f xs = concat (map f xs)
Using that:
solution2 :: [Integer]
solution2 = concatMap (\x -> map (\y -> x*10 + y) [4, 5, 6]) [1, 2, 3]
Other people have mentioned list comprehensions and the list monad, but those really bottom down to nested uses of concatMap.
Because do notation and the list comprehension have been said already. The only other option I know is via the liftM2 combinator from Control.Monad. Which is the exact same thing as the previous two.
liftM2 (\a b -> a * 10 + b) [1..3] [4..6]
The general solution of the concatenation of two lists of integers is this:
concatInt [] xs = xs
concatInt xs [] = xs
concatInt xs ys = [join x y | x <- xs , y <- ys ]
where
join x y = firstPart + secondPart
where
firstPart = x * 10 ^ lengthSecondPart
lengthSecondPart = 1 + (truncate $ logBase 10 (fromIntegral y))
secondPart = y
Example: concatInt [1,2,3] [4,5,6] == [14,15,16,24,25,26,34,35,36]
More complex example:
concatInt [0,2,10,1,100,200] [24,2,999,44,3] == [24,2,999,44,3,224,22,2999,244,23,1024,102,10999,1044,103,124,12,1999,144,13,10024,1002,100999,10044,1003,20024,2002,200999,20044,2003]

Haskell function application and currying

I am always interested in learning new languages, a fact that keeps me on my toes and makes me (I believe) a better programmer. My attempts at conquering Haskell come and go - twice so far - and I decided it was time to try again. 3rd time's the charm, right?
Nope. I re-read my old notes... and get disappointed :-(
The problem that made me lose faith last time, was an easy one: permutations of integers.
i.e. from a list of integers, to a list of lists - a list of their permutations:
[int] -> [[int]]
This is in fact a generic problem, so replacing 'int' above with 'a', would still apply.
From my notes:
I code it first on my own, I succeed. Hurrah!
I send my solution to a good friend of mine - Haskell guru, it usually helps to learn from gurus - and he sends me this, which I am told, "expresses the true power of the language, the use of generic facilities to code your needs". All for it, I recently drank the kool-aid, let's go:
permute :: [a] -> [[a]]
permute = foldr (concatMap.ins) [[]]
where ins x [] = [[x]]
ins x (y:ys) = (x:y:ys):[ y:res | res <- ins x ys]
Hmm.
Let's break this down:
bash$ cat b.hs
ins x [] = [[x]]
ins x (y:ys) = (x:y:ys):[ y:res | res <- ins x ys]
bash$ ghci
Prelude> :load b.hs
[1 of 1] Compiling Main ( b.hs, interpreted )
Ok, modules loaded: Main.
*Main> ins 1 [2,3]
[[1,2,3],[2,1,3],[2,3,1]]
OK, so far, so good. Took me a minute to understand the second line of "ins", but OK:
It places the 1st arg in all possible positions in the list. Cool.
Now, to understand the foldr and concatMap. in "Real world Haskell", the DOT was explained...
(f . g) x
...as just another syntax for...
f (g x)
And in the code the guru sent, DOT was used from a foldr, with the "ins" function as the fold "collapse":
*Main> let g=concatMap . ins
*Main> g 1 [[2,3]]
[[1,2,3],[2,1,3],[2,3,1]]
OK, since I want to understand how the DOT is used by the guru, I try the equivalent expression according to the DOT definition, (f . g) x = f (g x) ...
*Main> concatMap (ins 1 [[2,3]])
<interactive>:1:11:
Couldn't match expected type `a -> [b]'
against inferred type `[[[t]]]'
In the first argument of `concatMap', namely `(ins 1 [[2, 3]])'
In the expression: concatMap (ins 1 [[2, 3]])
In the definition of `it': it = concatMap (ins 1 [[2, 3]])
What!?! Why?
OK, I check concatMap's signature, and find that it needs a lambda and a list, but that's
just a human thinking; how does GHC cope? According to the definition of DOT above...
(f.g)x = f(g x),
...what I did was valid, replace-wise:
(concatMap . ins) x y = concatMap (ins x y)
Scratching head...
*Main> concatMap (ins 1) [[2,3]]
[[1,2,3],[2,1,3],[2,3,1]]
So... The DOT explanation was apparently
too simplistic... DOT must be somehow clever enough to understand
that we in fact wanted "ins" to get curri-ed away and "eat" the first
argument - thus becoming a function that only wants to operate on [t]
(and "intersperse" them with '1' in all possible positions).
But where was this specified? How did GHC knew to do this, when we invoked:
*Main> (concatMap . ins) 1 [[2,3]]
[[1,2,3],[2,1,3],[2,3,1]]
Did the "ins" signature somehow conveyed this... "eat my first argument" policy?
*Main> :info ins
ins :: t -> [t] -> [[t]] -- Defined at b.hs:1:0-2
I don't see nothing special - "ins" is a function that takes a 't',
a list of 't', and proceeds to create a list with all "interspersals". Nothing about "eat your first argument and curry it away".
So there... I am baffled. I understand (after an hour of looking at the code!) what goes on, but... God almighty... Perhaps GHC makes attempts to see how many arguments it can "peel off"?
let's try with no argument "curried" into "ins",
oh gosh, boom,
let's try with one argument "curried" into "ins",
yep, works,
that must be it, proceed)
Again - yikes...
And since I am always comparing the languages I am learning with what I already know, how would "ins" look in Python?
a=[2,3]
print [a[:x]+[1]+a[x:] for x in xrange(len(a)+1)]
[[1, 2, 3], [2, 1, 3], [2, 3, 1]]
Be honest, now... which is simpler?
I mean, I know I am a newbie in Haskell, but I feel like an idiot... Looking at 4 lines of code for an hour, and ending up assuming that the compiler... tries various interpretations until it finds something that "clicks"?
To quote from Lethal weapon, "I am too old for this"...
(f . g) x = f (g x)
This is true. You concluded from that that
(f . g) x y = f (g x y)
must also be true, but that is not the case. In fact, the following is true:
(f . g) x y = f (g x) y
which is not the same.
Why is this true? Well (f . g) x y is the same as ((f . g) x) y and since we know that (f . g) x = f (g x) we can reduce that to (f (g x)) y, which is again the same as f (g x) y.
So (concatMap . ins) 1 [[2,3]] is equivalent to concatMap (ins 1) [[2,3]]. There is no magic going on here.
Another way to approach this is via the types:
. has the type (b -> c) -> (a -> b) -> a -> c, concatMap has the type (x -> [y]) -> [x] -> [y], ins has the type t -> [t] -> [[t]]. So if we use concatMap as the b -> c argument and ins as the a -> b argument, then a becomes t, b becomes [t] -> [[t]] and c becomes [[t]] -> [[t]] (with x = [t] and y = [t]).
So the type of concatMap . ins is t -> [[t]] -> [[t]], which means a function taking a whatever and a list of lists (of whatevers) and returning a list of lists (of the same type).
I'd like to add my two cents. The question and answer make it sound like . is some magical operator that does strange things with re-arranging function calls. That's not the case. . is just function composition. Here's an implementation in Python:
def dot(f, g):
def result(arg):
return f(g(arg))
return result
It just creates a new function which applies g to an argument, applies f to the result, and returns the result of applying f.
So (concatMap . ins) 1 [[2, 3]] is saying: create a function, concatMap . ins, and apply it to the arguments 1 and [[2, 3]]. When you do concatMap (ins 1 [[2,3]]) you're instead saying, apply the function concatMap to the result of applying ins to 1 and [[2, 3]] - completely different, as you figured out by Haskell's horrendous error message.
UPDATE: To stress this even further. You said that (f . g) x was another syntax for f (g x). This is wrong! . is just a function, as functions can have non-alpha-numeric names (>><, .., etc., could also be function names).
You're overthinking this problem. You can work it all out using simple equational reasoning. Let's try it from scratch:
permute = foldr (concatMap . ins) [[]]
This can be converted trivially to:
permute lst = foldr (concatMap . ins) [[]] lst
concatMap can be defined as:
concatMap f lst = concat (map f lst)
The way foldr works on a list is that (for instance):
-- let lst = [x, y, z]
foldr f init lst
= foldr f init [x, y, z]
= foldr f init (x : y : z : [])
= f x (f y (f z init))
So something like
permute [1, 2, 3]
becomes:
foldr (concatMap . ins) [[]] [1, 2, 3]
= (concatMap . ins) 1
((concatMap . ins) 2
((concatMap . ins) 3 [[]]))
Let's work through the first expression:
(concatMap . ins) 3 [[]]
= (\x -> concatMap (ins x)) 3 [[]] -- definition of (.)
= (concatMap (ins 3)) [[]]
= concatMap (ins 3) [[]] -- parens are unnecessary
= concat (map (ins 3) [[]]) -- definition of concatMap
Now ins 3 [] == [3], so
map (ins 3) [[]] == (ins 3 []) : [] -- definition of map
= [3] : []
= [[3]]
So our original expression becomes:
foldr (concatMap . ins) [[]] [1, 2, 3]
= (concatMap . ins) 1
((concatMap . ins) 2
((concatMap . ins) 3 [[]]))
= (concatMap . ins) 1
((concatMap . ins) 2 [[3]]
Let's work through
(concatMap . ins) 2 [[3]]
= (\x -> concatMap (ins x)) 2 [[3]]
= (concatMap (ins 2)) [[3]]
= concatMap (ins 2) [[3]] -- parens are unnecessary
= concat (map (ins 2) [[3]]) -- definition of concatMap
= concat (ins 2 [3] : [])
= concat ([[2, 3], [3, 2]] : [])
= concat [[[2, 3], [3, 2]]]
= [[2, 3], [3, 2]]
So our original expression becomes:
foldr (concatMap . ins) [[]] [1, 2, 3]
= (concatMap . ins) 1 [[2, 3], [3, 2]]
= (\x -> concatMap (ins x)) 1 [[2, 3], [3, 2]]
= concatMap (ins 1) [[2, 3], [3, 2]]
= concat (map (ins 1) [[2, 3], [3, 2]])
= concat [ins 1 [2, 3], ins 1 [3, 2]] -- definition of map
= concat [[[1, 2, 3], [2, 1, 3], [2, 3, 1]],
[[1, 3, 2], [3, 1, 2], [3, 2, 1]]] -- defn of ins
= [[1, 2, 3], [2, 1, 3], [2, 3, 1],
[1, 3, 2], [3, 1, 2], [3, 2, 1]]
Nothing magical here. I think you may have been confused because it's easy to assume that concatMap = concat . map, but this is not the case. Similarly, it may seem like concatMap f = concat . (map f), but this isn't true either. Equational reasoning will show you why.

Resources